Implications and pathophysiology of neuroinflammation in pediatric patients with traumatic brain injury: an updated review - Shah, Shalin S.; Shetty, Arya J.; Johnston, David T.; Hanan, Caroline L.; O’Reilly, Brendan T.; Skibber, Max A.; Massoud, Ahmed T.; Zhu, Banghe; Sevick-Muraca, Eva M.; Juranek, Jenifer; Cox, Charles S.; Shah, Manish N. (Frontiers in Neuroscience, 2025)
Traumatic Brain Injury (TBI) in children is a profound public health issue with the potential to disrupt cognitive, behavioral, and psychosocial development significantly. This review provides an updated examination of the role of neuroinflammation in pediatric TBI, emphasizing its dual impact on injury progression and recovery. Highlighted is the complex interplay of primary and secondary injury mechanisms, including the critical contributions of neuroinflammatory responses mediated by central and peripheral immune cells. Advances in biomarker identification and imaging techniques are discussed, showcasing how tools like diffusion tensor imaging (DTI) and positron emission tomography (PET) enhance our understanding of neuroinflammatory processes. The review also explores current therapeutic strategies targeting neuroinflammation, underscoring emerging treatments such as pharmacologic agents that modulate immune responses and novel therapies like stem cell interventions. This comprehensive review seeks to deepen the understanding of neuroinflammation’s pathophysiological roles in pediatric TBI and propose directions for future clinical and research efforts.